Effects of Activation Process on Catkin Derived Carbon Materials and Its Electrochemical Performance as Matrix in Cathode of Li‐S Battery. Issue 38 (13th October 2020) - Yan, Yinglin; Chen, Shiyu; Fan, Chaojiang; Lin, Jiaming; Fan, Hua; Feng, Zufei; Wang, Juan; Xu, Yunhua; You, Caiyin; Yang, Rong
Abstract: Willow catkin was selected as raw material to fabricated carbon matrix in cathode of lithium‐sulfur (Li−S) battery due to its unique tubular morphology. The effects of activation time on the microstructure and electrochemical properties were investigated. The direct pyrolysis product inherited the tube‐like morphology. After activated by KOH under high temperature once, the microtubes were shorten and pressed as ribbon‐like. Meanwhile abundant micropores were formed in the tube wall. Further activatated the product twice, the original tube‐like microstructure was collapsed. Thus the results demonstrated that extending the activation time greatly affected the microstructure of carbon product. Furthermore, the sample activated once exhibited the largest specific surface area of 2033.09 m 2  g −1 and the largest sulfur loading ratio (71.1 %). Moreover, the suitable activated sample exhibited the highest specific discharge capacity (1365.8 mAh g −1 ) and the best cycling performance. Consequently, the activation process played an important role in the microstructure and electrochemical performance of catkin derived carbon matrix in Li−S battery. Abstract : Willow catkin was selected as raw material to fabricate porous carbon material due to its tubular microstructure in nature, which exhibited high specific surface area and efficient mass transfer. The activation process imposed significant influence on microstructure and electrochemical performance of carbon product as matrix in cathode of Li−S battery.